2015
DOI: 10.1007/s00394-015-0853-x
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status from childhood to adulthood in females living in North-East Italy: Iodine deficiency is still an issue

Abstract: Dietary iodine status declines from childhood to adulthood in females due to different eating habits. A mild iodine deficiency emerged in women of child-bearing age that could have consequences during pregnancy and lactation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
4
11
1
Order By: Relevance
“…Although unexpected increases were observed at day 14, the observed increase in milk iodide levels is not of great concern for public health as the levels never exceed maximum recommended level of 500 μg/L. In many countries, iodine from milk or dairy products is considered an important component of dietary iodine intake (Andersson and others ; Soriguer and others ; Watutantrige and others ) and milk iodine levels reported in this study would also support the prevention of iodine deficiency.…”
Section: Discussionsupporting
confidence: 56%
“…Although unexpected increases were observed at day 14, the observed increase in milk iodide levels is not of great concern for public health as the levels never exceed maximum recommended level of 500 μg/L. In many countries, iodine from milk or dairy products is considered an important component of dietary iodine intake (Andersson and others ; Soriguer and others ; Watutantrige and others ) and milk iodine levels reported in this study would also support the prevention of iodine deficiency.…”
Section: Discussionsupporting
confidence: 56%
“…Indeed, Olivieri et al [5] reported that iodized salt accounted for 55% of salt sales in Italy in 2012. Moreover, in recent surveys in northeastern Italy, 70-80% of families declared that they used iodized salt daily [9,11], while in a study conducted in Calabria the percentage of families using iodized salt was 64-82% in rural-urban areas [23]. Of the 136 subjects attending our Center for Secondary Hypertension, 62% declared using iodized salt, since, at the beginning of the study, all these patients had had a consultation with a dietitian and had received written nutritional advice [16].…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional and cultural variables can influence iodine intake. Iodized salt and milk are the main foods that influence UIC in surveys conducted among Italian children [9,11]. Major barriers to iodine intake seem to be immigrant status and poverty, as documented in a cross-sectional survey recently conducted among around 3400 women referred to non-governmental organizations for their health needs [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the iodine intake, which is already often below the indicated values at baseline, needs to be increased at least to 50% [55]. However, several surveys have demonstrated how frequent iodine deficiency is in pregnant women, both in developed and in developing countries [56-58]. Recent studies investigating the effects of hypothyroxinemia on fetal neurodevelopment, in general terms, have reported a negative correlation, especially when it occurs during the first trimester [30].…”
Section: Maternal Hypothyroidismmentioning
confidence: 99%